Synthesis of Pure and High-Quality Biodiesel from Waste Frying Oil Using CaO Prepared from Waste Coralline Sand - Singh R.; Pradhan G.; Pradhan S.; Madhu D. (My University, 2025)
Biodiesel is projected to replace the conventional diesel which is naturally occurring from a non-renewable resource called petroleum. Biodiesel generally prepared from bioresources and improves rural economy. The present research focuses on synthesis of biodiesel from waste cooking oil using catalyst generated from waste material. Waste coralline sand degraded from parent coral reef rock was used to make high purity and low cost CaO, and used in the production of biodiesel as an effective heterogeneous solid base catalyst. The calcination temperature was held at 800 °C for 3.5 h, yielding a high purity CaO catalyst. Well-known tools namely XRD, FT-IR, and TGA were employed to characterize the catalyst that was obtained. Elemental analysis and surface morphology were observed with SEM–EDX, respectively. To produce biodiesel, each batch went through a succession of transesterification reactions. Each experiment examined how the co-solvent changed the yield of biodiesel. Biodiesel of high grade and purity was produced and analysed using 1H NMR and FT-IR spectra. There are some variables which adversely affected biodiesel yield, like reaction time, temperature, molar ratio, and concentration of the catalyst. The density, kinematic viscosity, cloud point, and other properties of synthesised biodiesel were investigated using ASTM guidelines. It was established that the developed CaO catalyst was reused up to 5 times without substantially degrading its catalytic activity. Graphical Abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer Nature B.V. 2023.